A New Type of Construction Evidenced by Ship 17 of Thonis‐Heracleion. (2nd May 2014) - Belov, Alexander
<x xml:space="preserve">Abstract</x> Ship 17 is the first of 63 vessels from the submerged city of Thonis‐Heracleion in Egypt to have been excavated. The peculiar constructional features of this ship, which dates to the Late Period (722–332 BC), allow us to argue for a previously undocumented type of construction that finds parallels in Herodotus' description of a Nilotic freighter known as a baris (History, 2.96, c.450 BC). The aim of this article is to outline the main characteristics and the possible sequence of construction of Ship 17.